The construction of the project evaluation concept in a team of teachers - Da Matta, Eduardo Nadaleto (2018)
The school is the setting where students seek knowledge. In turn, it is extremely important to measure the knowledge obtained, without that, there is no parameter to know the effectiveness of the work performed. It is necessary to overcome the traditional evaluation system, which is composed of tests, work, seminars, which but often is not aligned with all the dimensions of the desired learning. The inadequacy of the evaluation process is due to the fact that learning goes beyond the specific technical knowledge of the disciplines, which is not always well understood by teachers, so that the transversal skills students need to develop in school are not adequately assessed. The competences necessary to the modern professional require the restructuring of the evaluation process, aligned with strategies and new learning objectives. In particular, for transverse skills, it is necessary to identify indicators to measure student’s learning at the school process. In order to promote the improvement on the process and evaluation instruments, an engineering school have been organizing a work with a group of teachers, to analyze and reflect on objective and ways of evaluating the students. They are workshops in which teachers are too, encouraged to create rubrics for these assessments. The aim of this work is to identify the perception of the teachers about the evaluation process in projects, as well as to identify what instruments that they propose to evaluate the transversal skills in the engineering student’s qualification. To the school, there is the interest to develop rubrics that become the standard of evaluation of projects developed by students. The question is how to promote an assessment to measure and gives feedback to the student about the development of transversal competences?.